1992
DOI: 10.1002/j.1460-2075.1992.tb05232.x
|View full text |Cite
|
Sign up to set email alerts
|

A fungal mating type protein that regulates sexual and asexual development contains a POU-related domain.

Abstract: The A mating type factor of the fungus Coprinus cinereus regulates essential steps in sexual development. Here we describe features of one of the four specificity genes of the A42 factor. By transformation we show that the gene regulates not only sexual development but also asexual sporulation. DNA sequence analysis shows that the gene beta 1–1, encodes a protein with a DNA binding motif and is thus likely to be a transcription factor. The DNA binding domain is an unusual homeodomain with D replacing the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0
4

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 66 publications
5
45
0
4
Order By: Relevance
“…It is not known whether the A mating-type products are positive or negative regulators of development, since morphological observations do not show whether a regulatory effect is direct or indirect. Analysis of monokaryons transformed with A genes of another specificity ("A on" transformants) revealed a negative function of compatible A genes on the production of oidia and positive effects not only on the formation of clamp cells but also on the formation of chlamydospores, hyphal knots, and fruiting-body initials (232,258,261,307,358,477), consistent with the earlier observations with common B heterokaryons and Amut homokaryons (see above) ( Table 1). The mating-type-encoded transcription factors of C. cinereus and other basidiomycetes (S. commune and Ustilago spp.)…”
Section: Mating-type Locisupporting
confidence: 86%
See 3 more Smart Citations
“…It is not known whether the A mating-type products are positive or negative regulators of development, since morphological observations do not show whether a regulatory effect is direct or indirect. Analysis of monokaryons transformed with A genes of another specificity ("A on" transformants) revealed a negative function of compatible A genes on the production of oidia and positive effects not only on the formation of clamp cells but also on the formation of chlamydospores, hyphal knots, and fruiting-body initials (232,258,261,307,358,477), consistent with the earlier observations with common B heterokaryons and Amut homokaryons (see above) ( Table 1). The mating-type-encoded transcription factors of C. cinereus and other basidiomycetes (S. commune and Ustilago spp.)…”
Section: Mating-type Locisupporting
confidence: 86%
“…Paralogous genes from the same A haplotype and also allelic versions from other A haplotype are very different in sequence, with the highest conservation in the regions containing the homeodomain motifs. Paralogous genes have a DNA sequence identity between 40 and 50%, allelic genes DNA homologies between 60 and 70% (16,131,258,308,477). Domain swaps indicated that allele specificity resides within the highly variable N termini of the proteins and subsequent in vitro studies on Cterminally truncated proteins showed that the 120-to 150-aa N termini are indeed discriminating HD1-HD2 protein dimerization domains (22,258).…”
Section: Vol 64 2000 Developmental Processes In Coprinus Cinereusmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that the most obvious explanation is that the developmental defects were a consequence of the cell cycle impairment. In C. cinerea developmental decisions are controlled by environmental conditions as well as by an appropriated balance of the mating-type regulators (Tymon et al 1992;Kües et al 1998Kües et al , 2002b. Therefore it seems likely that any condition affecting the correct dose of mating-type regulators will affect the further developmental decisions.…”
Section: Discussionmentioning
confidence: 99%